As afrografias e suas ressonâncias nas performances de poesia falada no slam - Rogério Meira Coelho (2023)
This doctorate work in Literary Studies (UFMG) seeks to activate the connections and approximations of the term Afrografias, created by PhD Leda Maria Martins, who is a congo queen of the Reinado do Jatobá, with the performance arts, made by black poets of slam, in Brazil, a spoken poetry competition broadcast worldwide. The analyzes will rely on the audiovisual element as support and fundamental material for the recognition of the hypotheses raised here. As a theoretical reference, we consider the importance of dialoguing with the texts of Leda Maria Martins: Afrografias da Memória: o reinado do rosário do jatobá (1997); Performance do Tempo Espiralar (2021); Performances da Oralitura: Corpo lugar da memória (2003) e A cena em sombras (1995). As a complementary bibliography, we bring here some works and authors that reveal their connections and contributions to the analysis of Performance art, such as Richard Schechner (2002), Diana Taylor (2011), Denise Ferreira da Silva (2019) and Paul Zumthor (2007), that one being fundamental to the discussions that point to the slam as the ritual. Thus, the research will present, together with the audiovisual element, texts and exploratory conversations of poets chosen from the slam, which contribute to the connections with the Afrographies, in the sense of revealing, through the performances and resonance (and their crossroads elements, crossings and hybrids) transcreations of Afro-Brazilian and African cultures, especially artistic ones, those based on issues of racism and the black culture in the Brazilian diaspora.